ADHD medication prescription: Effects of child, sibling, parent and general practice characteristics. (December 2016) - Heins, Marianne J; Bruggers, Inge; Dijk, Liset van; Korevaar, Joke C
Many children receive attention-deficit hyperactivity disorder (ADHD) medication, but factors that determine medication prescription are largely unknown. This study aimed to determine the relative impact of factors on the child, family and general practitioner (GP) practice level on ADHD medication prescription. We included 1259 Dutch children aged 6–18 years with a diagnostic code of ADHD or related behavioural problems (ICPC codes P20-P22) in NIVEL primary care database. Using multilevel analyses, we examined predictors of ADHD medication prescription. Children diagnosed as 'hyperactive' were 16 times more likely to be prescribed ADHD medication than those with 'behavioural concerns'. Children with a parent or sibling receiving ADHD medication were three to four times more likely to be prescribed ADHD medication themselves. Children from GP practices with a high percentage of children with ADHD were twice as likely to be prescribed ADHD medication. Concluding, factors on the individual, family and GP practice level determine ADHD medication prescription. Future research into the decision-making process for ADHD medication is warranted.